Use of Quantitative Electroencephalography Biomarker in Characterizing Mild Cognitive Impairment in Malaysian Elderly - Samhani, Ismail; Badya, Norhidayah; Reza, Mohammed Faruque; Simbak, Nordin (International Journal of Human and Health Sciences (IJHHS), 2020)
The elderly population rising rapidly in Malaysia and contributes to the increasing number of cognitive problems including mild cognitive impairment (MCI). However, due to limited information regarding this problem which may progress towards severe neurologic degeneration, this problem rarely diagnosed and left untreated. Hence, the use of electroencephalography (EEG) biomarker is seen to be important with the spectral power, coherence and synchronization between the both halves of brain explain the pathophysiology underlined. This method is becoming popular for its capabilities in quantifying changes in brain electrical activity and provide early signs of brain impairment. This paper reviews the incidence of mild cognitive impairment in elderly as an early cognitive deterioration signal. It continues with the role of quantitative EEG analysis in providing the physiological meaning of their brain. This paper also provides the information about neurochemical changes which associated with MCI. In addition, this paper proposes an idea of study towards examining physiology, neurochemicals, diet and lifestyles to promote healthy lifestyle in elderly. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 267-270